Peran Tokoh Masyarakat Dalam Pemilihan BPD - Saputra, Indra; Dalimunthe, Dermina (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research is entitled The Role of Community Leaders in the Election of the Village Consultative Body in Sipange Godang Village, South Tapanuli Regency. The problem in this research is how the role of community leaders in the election of members of the Village Consultative Body and the selection system for members of the Village Consultative Body. The formulation of the problem in this research is how the role of community leaders in the selection of members of the Village Consultative Body in Sipange Godang Village, Sayur Matinggi District, South Tapanuli Regency and how the system for selecting members of the Village Consultative Body in Sipange Godang Village, Sayur Matinggi District, South Tapanuli Regency. So the purpose of this research is to find out the role of community leaders in the election of members of the Village Consultative Body and the selection system for members of the Village Consultative Council. To obtain the results of this study, researchers used a type of field research (Field research) which is descriptive qualitative. The data collection used is interview technique, observation, and documentation data. While the data analysis technique was carried out using several steps, namely editing, verification, data analysis and drawing conclusions. Based on the results of the research, the role of community leaders in the selection of members of the Village Consultative Body (BPD) in Sipange Godang Village, Sayur Matinggi District, South Tapanuli Regency is as a motivator, dynamist, and as a social control. The election system for members of the Village Consultative Body is carried out by means of a consensus deliberation system, lobbying system, and voting system.